mekanisme tata kelola dan profitabilitas terhadap green banking disclosure - tita, alma (LPPM STIE Mujahidin Tolitoli, 2025)
Banks in Indonesia have begun to prove their seriousness in responding to environmental issues through green banking program, it is a bank's effort to prioritize sustainable aspects in financing and operational activities. The Financial Services Authority regulation requires banks to communicate the implementation of green banking to stakeholders through reports prepared by banks. Disclosure of green banking has shown an increasing trend where banks have performed well although the level of disclosure is different. This study aims to analyze the effect of corporate governance mechanisms and profitability on green banking disclosure. The research design is quantitative. Corporate governance mechanisms represented by board size of directors, independent commissioners, and institutional ownership. The data used is in the form of annual reports and sustainability reports. The data analysis technique used is multiple linear regression. The results showed that the corporate governance mechanism represented by board size of directors had a positive effect on green banking disclosure, while independent commissioners and institutional ownership had no effect on green banking disclosure. Profitability has no effect on green banking disclosure because high and low profitability does not guarantee that the company will disclose information about green banking. The implications of the research show that managers as internal parties play the most role in presenting information so that it is hoped that in the future they can present information as completely as possible so that information asymmetry does not occur.